Mobile phones and minds: linking usage to stress and academic performance in undergraduates - Maladar, Umme Ruman; Dandannavar, Vijaya S. (International Journal of Research in Medical Sciences, 2025)
Background: Mobile phones have become ubiquitous among students, providing easy access to communication and information. However, excessive use has been associated with negative outcomes, including decreased academic performance and increased psychological stress. Understanding the relationship between mobile phone usage, stress and academic achievement is essential to promote healthy study habits and overall well-being among undergraduate students. Methods: This cross-sectional study included 110 first-year Allied Health and Physiotherapy students from JN Medical College, Belagavi, who provided informed consent. Participants completed a structured questionnaire detailing demographic information, mobile phone usage patterns and study habits. Academic performance was assessed using self-reported grades and recent examination scores, while stress levels were evaluated using a standardized stress assessment scale. Results: Students reporting higher daily mobile phone usage exhibited significantly lower academic performance compared with those with limited usage (p<0.05). Additionally, frequent mobile phone use was associated with elevated stress levels, suggesting a direct relationship between screen time, psychological stress and learning outcomes. Students who managed mobile phone usage effectively demonstrated better academic scores and lower stress, highlighting the potential impact of controlled use on educational achievement and mental health. Conclusions: Excessive mobile phone usage among undergraduates is linked to poorer academic performance and higher stress levels. Awareness and strategies to regulate mobile phone use may help improve learning outcomes and reduce stress in this population.